Further characterization of atypical features in auriculocondylar syndrome caused by recessive PLCB4 mutations. Issue 9 (2nd August 2013) - Kido, Yasuhiro; Gordon, Christopher T.; Sakazume, Satoru; Bdira, Eya Ben; Dattani, Mehul; Wilson, Louise C.; Lyonnet, Stanislas; Murakami, Nobuyuki; Cunningham, Michael L.; Amiel, Jeanne; Nagai, Toshiro
Abstract Auriculocondylar syndrome (ACS) is a branchial arch syndrome typically inherited in an autosomal dominant fashion. Patients with ACS display the following core symptoms with varying severity: a specific malformation of the external ear, known as a "question mark ear, " micrognathia and mandibular condyle hypoplasia. Recently, phospholipase C, β 4 (PLCB4) mutations were identified as the major cause of autosomal dominant ACS, with mutations of the PLCB4 catalytic domain predicted to have a dominant negative effect. In addition, one ACS patient born to related parents harbored a homozygous partial deletion of PLCB4, and presented with ACS plus central apnea and macropenis; these features had not been previously reported in association with ACS. His parents, each with a heterozygous partial PLCB4 deletion, were phenotypically normal, suggesting autosomal recessive inheritance of ACS, with complete loss of function of PLCB4 predicted in the patient. We herein describe two brothers with ACS caused by compound heterozygous splice site mutations in PLCB4. The patients were born to the same unrelated and healthy parents, with each parent harboring one of the mutations, indicating autosomal recessive ACS. Both patients reported here had mixed apneas, gastrointestinal transit defects and macropenis, in addition to typical craniofacial features of ACS. This is the first example of ACS caused by compound heterozygous splice site mutations in PLCB4, the second autosomal recessive case of ACS confirmed by molecular analysis, and strengthens the link between complete loss of function of PLCB4 and extra‐craniofacial features. © 2013 Wiley Periodicals, Inc.